Alienation of Female Body in the Selected Stories of Parijat - Nepal, Khagendra Prasad (Haimaprabha, 2023)
This paper analyzes the much neglected aspects of alienation of female body with particular reference to the selected stories, Tiuriko Phul, Pairiyako Gandha, and Salgiko Balatkrit Anshu by prominent Nepali writer, Parijat dealing with the female body alienation. The article focuses on how female bodies have been alienated from their selves; how these female characters, Lati and Salgi do not have the sense of being distanced from their own selves. It uses qualitative methodology and takes feminism as a theoretical tool to interpret and analyze the primary texts. Instead of focusing on the analysis of the theme of the text, the article focuses on analysis of the text in concern with female body as portrayed in the stories. The female characters in the mentioned stories are physically assaulted, raped, and coerced time and again. Their bodies become the site where men enact violence. This study argues that these female characters become the victim of violence just because they are women. It also makes an attempt to bring the readers home as to how women suffer from gender-based violence in patriarchy.